Importance of Surface Analysis in Contributing to Tribology for Achieving Carbon Neutral Society - Sasaki, Shinya (Journal of Surface Analysis, 2024)
The improvement of tribology technology, which deals with friction, wear, and lubrication phenomena in mechanical systems, is greatly influenced by the advancement of surface analysis technology. As we strive towards realizing a carbon-neutral society, there are numerous new technological challenges that need to be addressed. To solve these challenges, it is essential to gain a more detailed understanding of the phenomena occurring at the friction interfaces and to link this knowledge to the development of friction materials and lubricants. In this context, we would like to introduce the required information for analyzing tribological surfaces, along with the expectations for the future.